Prognosis of impacted canines according to their position in the upper maxillary using different radiographic analyzes - Diaz-Reissner, Clarisse (2022)
Introduction: Canine impaction is an anomaly in which the tooth is prevented from erupting. It occurs when eruption has been delayed and there is radiographic evidence. Objective: To determine the prognosis of impacted canines according to their position in the maxilla by means of different analyses: Ericson & Kurol, Warford and Power & Short; in patients attending private clinics in the city of Asuncion from 2015 to 2020. Methodology: The design is observational descriptive, cross-sectional, using panoramic radiograph measurements. Results: The sample consisted of 37 patients and the 48 canines. It was found that the presence of impacted canines was more frequent in women (69.44%), with unilateral location (70.27%) and palatal position (68.75%). In more than half of the cases the prognosis was unfavorable, however, the concordance was only 75.00%. There was greater concordance in Warford's prognosis with that of Power & Short (95.91%), while the concordance was lower with that of Ericson & Kurol (81.25%). Conclusion: The frequency of impacted canines in a Paraguayan sample was higher in females, unilaterally located and positioned by palatine. Being unfavorable in more than half of the cases. It is suggested to combine the analyses for projection.